STUDY OF THE INFLUENCE OF THE POSITION OF THE TENDON GRAFT HAMSTRING MUSCLE ON THE STABILITY OF THE KNEE JOINT UNDER THE CONDITIONS OF PLASTICITY OF THE STRUCTURES OF THE POSTEROLATERAL ANGLE - Golovakha, Maxim; Panchenko, Serhii; Bondarenko, Stanislav; Bezverkhyi, Andrey (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
Damage to the posterolateral angle of the knee joint is an injury that occurs occasionally and can be isolated or combined with tears of the posterior or anterior cruciate ligaments. The key link of damage to the posterior lateral corner is the rupture of the tendon of the hamstring muscle, mained stabilizer of excess external rotation lower legs. Objective. Determine the optimal fixation position tendon graft on the posterior surface of the tibia subject to recovery of the hamstring muscle which ensuring the greatest stability of the lower leg during external rotation. Methods. Models of the knee joint were built with different attachment points of the popliteal graft muscle in the ANSYS software environment. The criteria for evaluating the effectiveness of selecting the fixation point of the transplant were chosen as the degree of movement of the finite parts elements of the model. Results. The smallest movements in all directions received in the case when the transplant fixed as far as possible outwards and upwards, near the joint surface. Maximum — in the direction of the coordinate axes, as well as full movement were recorded for the control model, in the absence of the hamstring tendon The nature of the distribution of displacement fields in all models p graft and control were identical. Biggest there were additional displacements in the direction of the x axis (outward). on the front border of the platform, and the largest negative (so far redins) on the back. The largest additional shifts to the sides the y (front) axes are fixed at the leftmost limit and the largest negative (back) — to the rightю Conclusions. In view of the stability of the lower leg during rotational loading, the most effective is fixation of the hamstring graft on the back surface of the fibula is as late as possible and closer to its cardiac surface, finished in this case, the dimensions are found to be the smallest in all directions. The greatest displacement in all directions obtained in the control model for less tendon hamstring muscle.